Effect of standardised surgical assessment and shared decision-making on morbidity and patient satisfaction after breast conserving therapy: A cross-sectional study. Issue 1 (January 2023) - Aristokleous, Iliana; Öberg, Johanna; Pantiora, Eirini; Sjökvist, Olivia; Navia, Jaime E.; Mani, Maria; Karakatsanis, Andreas
Abstract: Background: The role of oncoplastic breast conserving therapy (OPBCT) on physical function, morbidity and patient satisfaction has yet to be defined. Additionally, technique selection should be individualised and incorporate patient preference. The study aim was to investigate differences between "standard" (sBCT) and oncoplastic breast conservation (OPBCT) in patient-reported outcomes (PROs) when patients have been assessed in a standardised manner and technique selection has been reached through shared decision-making (SDM). Methods: This is a cross-sectional study of 215 women treated at a tertiary referral centre. Standardised surgical assessment included breast and lesion volumetry, definition of resection ratio, patient-related risk factors and patient preference. Postoperative morbidity and patient satisfaction were assessed by validated PROs tools (Diseases of the Arm, Shoulder and Hand-DASH and Breast-Q). Patient experience was assessed by semi-structured interviews. Results: There was no difference of the median values between OPBCT and sBCT in postoperative morbidity of the upper extremity (DASH 3.3 vs 5, p = 0.656) or the function of the chest wall (Breast-Q 82 vs 82, p = 0.758). Postoperative satisfaction with breasts did not differ either (Breast-Q 65 vs 61, p = 0.702). On the individual level, women that opted for OPBCT after SDM had improved satisfaction when compared to baseline (+3 vs −1, p = 0.001). Shared decision-making changed patient attitude in 69.8% of patients, leading most often to de-escalation from mastectomy. Conclusions: These findings support that a combination of standardised surgical assessment and SDM allows for tailored treatment and de-escalation of oncoplastic surgery without negatively affecting patient satisfaction and morbidity. Highlights: Standardised surgical assessment and shared decision-making lead to de-escalation of surgery Rationalised de-escalation of oncoplastic procedures does not affect outcomes Comparable postoperative functional and aesthetic outcomes regardless of surgical technique, if appropriate selection. Patient engagement is crucial for high satisfaction and positive experience Current algorithms have grey zones that may be addressed by this approach